Pengukuhan Budaya Patriarki dalam Novel Kartini karya Abidah El Khalieqy: Inauguration of Patriarchy in Kartini Novel Written by Abidah El Khalieqy - Nur Halifah (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2020)
Kartini novel that written by Abidah El Khalieqy is one of Indonesia's best works inspired by the true story of the hero with the motto "habis gelap, terbitlah terang". Its setting in Javanese land and the period of Dutch occupation, this novel shows the struggle of Kartini's character in fighting for her right to school like her brothers. This study aims to describe how Javanese culture becomes a very solid benchmark in creating boundaries for women to obtain equality with men. The mindset of the Javanese people that suppresses all movements of women in showing their identity in the public sphere, thus placing Kartini as an object of oppression carried out by those around her. Society as a determinant of every woman's footsteps and bases the word safety to strengthen the position of women in the domestic sphere.